Ridicule, Humour and Anti-Roma Racism in Romanian Television News: A Multimodal Critical Discourse Analysis - Petre Breazu (International Journal of Roma Studies, 2022)
Research shows that the public image of Roma on television reinforces existing prejudice and stereotypes in relation to illiteracy, criminality, primitiveness, or refusal to comply with societal norms and values. Scholars have drawn attention to the various forms of racism, both overt and covert, we find in media and political discourse.  Yet, one aspect that is less explored is the role of humor and ridicule in communicating anti-Roma racism. In this article, I conduct a multimodal critical discourse analysis (MCDA) of two news clips aired by one of the leading audio-visual stations in Romania. I draw attention to the use of humor and ridicule on public television as discursive strategies to belittle or conceal anti-Roma racism. I argue that such representations—where buffoonery, bad taste, cultural incompetence, and arrogance are highlighted—go beyond simple entertainment and cheap laughs but reinforce the inferior and marginalised status that Romani people have held for centuries on Romanian territories.